Predictors of either rapid healing or refractory reflux oesophagitis during treatment with potent acid suppression. Issue 6 (15th July 2014) - Kahrilas, P. J.; Persson, T.; Denison, H.; Wernersson, B.; Hughes, N.; Howden, C. W.
Summary Background Little is known regarding patient characteristics that influence the speed of reflux oesophagitis (RO) healing. Aim To investigate patient characteristics that may influence RO healing rates. Methods A post hoc analysis of clinical trial data for potent acid suppression treatment of RO (esomeprazole or AZD0865) was conducted. Group A underwent endoscopy at baseline, week 2 and 4, and group B at baseline, week 4 and 8. Group A patients were sub‐grouped as 'rapid' (healed at 2 weeks) or unhealed at 2 weeks. Group B patients were sub‐grouped as 'slow' (healed at 8 weeks, not at 4 weeks) or 'refractory' (not healed at 8 weeks). Logistic regression analysis was performed only for comparisons within group A. Results At 2, 4 and 8 weeks, RO had healed in 68%, 65% and 61% of patients unhealed at previous endoscopy, respectively. Low‐grade [vs. high‐grade (C or D)] RO was the only independent predictor of rapid healing in group A after logistic regression analysis. Significantly more rapid healers had low grade RO (A or B) at baseline than patients with refractory RO (84% vs. 49%; P < 0.001), and significantly more refractory patients had frequent regurgitation at baseline than slow healers (80% vs. 63%; P = 0.039). Conclusions Low‐ (vs. high‐) grade RO determines the most rapid benefit from acid suppression. Roughly two‐thirds of patients healed with each time increment of potent acid suppression therapy. This suggests that some unhealed patients may still heal with continued therapy and that truly refractory RO is rare. (ClinicalTrials.gov: NCT00206245).